Engineering of electronic and optical properties of ZnO thin films via Cu doping - 张国恒 邓小燕 薛华 向钢 (Chinese physics B, 2013)
ZnO thin films doped with different Cu concentrations are fabricated by reactive magnetron sputtering technique. XRD analysis indicates that the crystal quality of the ZnO：Cu film can be enhanced by a moderate level of Cu-doping in the sputtering process. The results of XPS spectra of zinc, oxygen, and copper elements show that Cu-doping has an evident and complicated effect on the chemical state of oxygen, but little effect on those of zinc and copper. Interestingly, further investigation of the optical properties of ZnO：Cu samples shows that the transmittance spectra exhibit both red shift and blue shift with the increase of Cu doping, in contrast to the simple monotonic behavior of the Burstein–Moss effect. Analysis reveals that this is due to the competition between oxygen vacancies and intrinsic and surface states of oxygen in the sample. Our result may suggest an effective way of tuning the bandgap of ZnO samples.